Psychological well-being in terms of tiger parenting among high school students in Yogyakarta City - Dewi, Ismira; Wati, Rinda Kumala (Jurnal Psikologi Terapan dan Pendidikan, 2025)
The adolescent phase is characterized by various high demands and expectations from the social environment, which significantly impact the psychological well-being of adolescents. Psychological well-being refers to an individual's capacity for psychological acceptance, which is essential for achieving life goals, values, and a sense of direction for the future. This study aims to empirically examine the effect of tiger parenting on the psychological well-being of adolescents. The methodology employed in this research utilizes a simple linear regression quantitative approach. The research scales used include the Tiger Parenting Scale and the Psychological Well-Being Scale. The sampling technique applied is incidental sampling. This research was conducted with 236 students from various high schools in the Yogyakarta City area. The data analysis technique employed in this study is simple linear regression analysis. The results of the regression analysis indicate a regression coefficient of 0.496, with a significance (p) level of 0.000 (p<0.05). Therefore, the hypothesis is accepted, suggesting that tiger parenting has a highly significant effect on psychological well-being. This finding suggests that parenting style has a significant influence on psychological well-being. Parents need to adopt appropriate parenting styles to enhance the psychological well-being of their children.